THE EFFECT OF EMOTIONAL INTELLIGENCE, QUALITY OF HUMAN RESOURCES AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLES IN THE BATAM SPECIAL KSOP OFFICE - Afwindra, Firdaus; Indrayani, Indrayani; Khaddafi, Muammar; Ngaliman, Ngaliman; Wibisono, Chablullah (CV. Radja Publika, 2022)
The purpose of this study was to analyze the effect of emotional intelligence, human resource quality and work discipline on employee performance with job satisfaction as an intervening variable at the Batam Special KSOP Office. The study population consisted of 98 civil servants and 34 honorary Batam Special KSOP Office. The sample selection method used is stratified random sampling, which is sampling from a stratified random population based on a certain level of frequency of all members of the population in this study the sample is honorary employees. The distribution of the questionnaire was carried out on 34honorary employees of the Batam Special KSOP Office. The data analysis technique used to solve the problem in this resear ch is quantitative analysis technique, namely path analysis with the application of multiple linear regression models using the help of the SPSS 24.0 program. The results of this study indicate that Emotional Intelligence and Work Discipline have a significant positive effect on Job Satisfaction while the Quality of Human Resources has a negative and insignificant effect on Job Satisfaction. Then, Emotional Intelligence has a positive and significant effect on employee performance. Quality of Human Resourcessignificant negative effect on Employee Performance. Furthermore, work discipline and job satisfaction have a positive and insignificant effect on employee performance.